ANALYSIS INFLUENCE RELATIONSHIP OF INTERNAL AND EXTERNAL ON STRATEGY AND SUSTAINABLE SUPPLY CHAINS MANAGEMENT ON OPERATIONAL PERFORMANCE OF FOOD AND BEVERAGES AGRO-INDUSTRIES - Dina Kartika Sari; Djoko Koestiono; Agustina Shinta (Socio-Economics/Agribusiness Department, 2021)
This research examines the influence of the relationship between internal and external factors on operational performance, beforehand an effective strategy supply chain management is needed to improve operational performance as a core strategic competency for better competitive advantage but companies need to evaluate actions that have environmental impacts, it is necessary practice sustainable supply chain management in a business. SEM-PLS analysis to examine the effect of the relationship between internal and external factor using a sample of 100 food and beverage agro-industries in the Province of East Java. The results showed that internal and external factors have a positive and significant effect on supply chain management strategy while on operational performance, although the influence of internal factors cannot be direct and external factors have a direct influence on operational performance, the practice sustainable supply chain management also has a direct effect as a mediating variable, between supply chain strategy variables on operational performance. This research is not only to find the right strategy for the food and beverage agro-industries but also to develop research on the importance of sustainable supply chain management practices in the food and beverage agro-industries.